Case report: Spinal cord stimulation in the treatment of pediatric erythromelalgia - Zuo, Lei; Su, Ai; Shi, Ying; Li, Nan; Chen, Shiyu; Yang, XiaoQiu (Frontiers in Neurology, 2023)
Introduction In children, erythromelalgia is a rare chronic pain syndrome characterized by erythema, severe burning pain, and itching of affected feet. Unfortunately, there is no definitive therapy available currently. Case report Here, we report a case of primary erythromelalgia and the treatment response in a 10-year-old boy, whose genetic findings for mutations in the SCN9A gene were positive and skin biopsy results were diagnosed as small fiber neuropathy, while he has suffered from excruciating burning pain, itching, erythema, and recurrent infections over the past 3 years. He did not respond well to conventional treatment, and the only way to receive minimal relief was to immerse his feet in ice water. After a successful trial of spinal cord stimulation (SCS), the implantable pulse generator (IPG) was successfully implanted without complications, and it proved partial response to therapy. Conclusion There is no specific, efficient treatment for pediatric erythromelalgia currently, but this case demonstrates neuromodulation serves as part of the multimodal regimen to treat pediatric erythromelalgia.